Upaya Meningkatkan Hasil Belajar Aqidah Akhlak Siswa Tentang Qada dan Qadar Melalui Model Pembelajaran Rotating Trio Exchange - Dalmiati Dalmiati (Publikasi Indonesia, 2023)
This study aims to improve the activeness and learning outcomes of Aqidah Akhlak grade VI students of SD Negeri 46 Toari Bombana, West Poleang District by applying the Rotating Trio Exchange type cooperative learning model. This type of research is classroom action research. The subjects of this study were class VI students totaling 23 students. The study was conducted in two cycles in which each cycle consisted of two meetings. Data collection techniques use learning activity observation sheets, learning outcomes tests, and documentation. The method for data analysis is quantitative descriptive analysis. The results of this study show that the application of the Rotating Trio Exchange type cooperative learning model can increase the activeness and learning outcomes of grade VI students of SD Negeri 46 Toari Bombana, West Poleang District, on learning Aqidah Akhlak, the subject matter of arguments about qada and qadar Allah SWT at SD Negeri 46 Toari Bombana, West Poleang District. The increase in student learning activity can be seen from each cycle. The average percentage of student learning activity in cycle I was 55.56% and increased in cycle II to 76.07%. The increase in student learning outcomes is seen from the increase in the percentage of completion of student learning outcomes. The percentage of completion of student learning outcomes during the pre-cycle was 44.44%, then increased during cycle I to 72.22% and increased again in cycle II to 100%.